2010
DOI: 10.1017/s1751731109990991
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and infectious disease: helminthological challenges to farmed ruminants in temperate regions

Abstract: In the UK, recent mean temperatures have consistently increased by between 18C and 48C compared to the 30-year monthly averages. Furthermore, all available predictive models for the UK indicate that the climate is likely to change further and feature more extreme weather events and a trend towards wetter, milder winters and hotter, drier summers. These changes will alter the prevalence of endemic diseases spatially and/or temporally and impact on animal health and welfare. Most notable among these endemic para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
133
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(141 citation statements)
references
References 150 publications
3
133
0
5
Order By: Relevance
“…The model predicted that the climatic conditions would become more favourable for the spread of fasciolosis over central and north-western Europe during the 2000s with an expanding northern distribution, which is consistent with the rising observed numbers of animal and human cases (Mas-Coma et al, 1999;van Dijk et al, 2010). This occurred in conjunction with other important factors such as reports of resistance to triclabendazole (Brennan et al, 2007).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The model predicted that the climatic conditions would become more favourable for the spread of fasciolosis over central and north-western Europe during the 2000s with an expanding northern distribution, which is consistent with the rising observed numbers of animal and human cases (Mas-Coma et al, 1999;van Dijk et al, 2010). This occurred in conjunction with other important factors such as reports of resistance to triclabendazole (Brennan et al, 2007).…”
Section: Discussionsupporting
confidence: 64%
“…Water is generally assumed to be crucial for the survival and development of the parasite's free living stages as well as the snail intermediate hosts (Ollerenshaw and Rowlands, 1959). Temperature and soil evapotranspiration co-determine development of the parasite and snail hosts, and this is the key determinant to the seasonality of this infection (van Dijk et al, 2010). Given the parasite's climate sensitivity, fasciolosis is expected to respond to climate change; however, its dependence on both temperature and moisture means that projected outcomes are not straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the change in environmental conditions due to climate change is the reason for the current widespread occurrence of fasciolosis (Kenyon et al, 2009;Van Dijk et al, 2010). Rapsch et al (2008) mention that the distribution of the free-living stages and the intermediate molluscan host, G. truncatula depend on a range of climatic factors, particularly temperature and rainfall, that also affect the survival of F. hepatica eggs and metacercarie.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are few data for STHs, empirical examples of climate-driven change have emerged from studies of high latitude systems in the Northern Hemisphere, primarily associated with ungulates [23,[27][28][29][30][31]. These studies have indicated the importance of both longterm cumulative change (represented as tipping points) and short-term ephemeral (or extreme) events as determinants of changing patterns of distribution and emergence of helminth-related diseases [23,[28][29][30].…”
Section: [ ( F I G U R E _ 1 ) T D $ F I G ]mentioning
confidence: 99%
“…Understanding linkages between climate and parasitism Research examining the causal relationships between climate, climate change and STH ecology is the focus of increased attention [23]. Understanding how STHs are likely to be affected by climate change requires an examination of the interactions between climate and parasite ecology and transmission ( Figure 1).…”
mentioning
confidence: 99%